The Effect of Solvent Ratio and Extraction Time on Antioxidant Activity and Flavonoid Concentration of Kedawung Leaf (Parkia Biglobosa) Through Microwave-Assisted Extraction (Jurnal Bahan Alam Terbarukan, 2022)
Kedawung (Parkia biglobosa) contains various ingredients such as alkaloids, saponins, tannins, flavonoids, and terpenoids. The flavonoid content in Kedawung is thought to have an antioxidant effect. Antioxidants are able to counteract free radicals that enter the body by donating electrons and binding them. Currently, the microwave-assisted extraction (MAE) method is widely used because the solute mass transfer from the sample matrix into the solvent is higher than the Soxhlet method. The following study aimed to know the effect of solvent ratio and extraction time on the extraction yield, flavonoid concentration, and antioxidant activity of kedawung leaf through microwave-assisted extraction. In this method, we used 40% ethanol to make the varied solute: solvent ratio such as 1:20, 1:30, 1:40, and 1:50. The extraction time used in this method was 4-7 minutes respectively. Microwave-assisted extraction has good performance to extract the active substance in Kedawung leaves. The highest yield 16.36%, total flavonoid content (57.32±2,2 mg QE/g extract), and DPPH scavenging activity (88.87±1.062%) was obtained in the extraction with a solids-solvent ratio of 1:40 g/mL, at an extraction time of 6 minutes. This method promises to take the active substance in a short time.